Pengaruh Transformational Leadership dan Transactional Leadership Terhadap Komitmen Kerja Serta Dampaknya Terhadap Kinerja Karyawan - Ummi Wahyuni; Fathorrahman Fathorrahman; Zainurrafiqi Zainurrafiqi; Runik Puji Rahayu; Devi Lestari Pramita Putri; Nurul Hidayati (BADAN PENERBIT STIEPARI PRESS, 2024)
Employee performance is a critical factor in enhancing the competitiveness of tourism MSMEs (Micro, Small, and Medium Enterprises) in Madura, particularly amid the evolving demands for service quality. Leadership plays a strategic role in shaping employee behavior and work commitment, where both transformational and transactional leadership styles significantly influence employee motivation and organizational loyalty. This study aims to examine and analyze the effect of transformational and transactional leadership on work commitment, as well as its impact on employee performance, with work commitment as a mediating variable. Employing a quantitative approach with a survey method, the study involved 170 employees from the tourism MSME sector in Madura. Data were collected through a structured questionnaire and analyzed using path analysis. The findings reveal that both transformational and transactional leadership have a positive and significant effect on work commitment. Furthermore, work commitment significantly influences employee performance. The results also confirm that work commitment significantly mediates the relationship between leadership styles and employee performance. These findings imply that strengthening leadership practices and systematically managing work commitment are key strategies to enhance productivity and effectiveness in the tourism MSME sector.